Could Not Sing in the Dead Heat: Liner Notes Under the Sun - Ramphalile, Molemo Karabo (University of the Witwatersrand, Johannesburg, 2022)
On the one hand we place blackness as a historical if inconsistent category inextricable with morbidity, disfavour, depravity, mystery, wretchedness, penumbra, opacity or absence of light, and the abyssal – in both secular and religious metaphysical symbolism. On the other hand we place space as a historical and physical category denoting area, range, clearance, scope, volume, expanse, lacunae, aperture, margin, and in its instance as verb – opening, arranging, ordering, placing, separating, and locating; which in cosmography, geography and cartography finds its varied imaginative and applied interpretation. We coalesce what is in both hands in order to envisage how blackness persistently becomes and comes to be the extractable property of sub-Saharan Africans. Through various ontological-cosmographic- geographic designations such as Torrid Zone, ‘land of the blacks’ or even terra nullius, we encounter visualisations of a territory and expanse that is always either completely devoid of people or inadequately peopled, that is, the territory whence blackness as inextricably embodied (or fleshened) exists and is cultivated. Blackness: not only does it determine our modes of being, or non-being, in this world, but for us in this study, it is also an experiential, experimental and analytical lens permitting the suggestion and scribing of historical narratives and discourses that centre the inveterate decentring of blacks. In the tradition of liner notes, this study is written in a performative relation to the subject or object at hand; there under the sun, in the dead heat.
A research report Submitted in fulfillment of the requirements for a Doctor of Philosophy , In the Faculty of Humanities , School of Social Sciences, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Torrid Zone; Blackness; Colonialism; Terra Nullius; Cartography; Early Modern; Space; South Africa; SDG-7: Affordable and clean energy